2015
DOI: 10.1016/j.bbabio.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis of mitochondria in cauliflower ( Brassica oleracea var. botrytis ) curds subjected to temperature stress and recovery involves regulation of the complexome, respiratory chain activity, organellar translation and ultrastructure

Abstract: The biogenesis of the cauliflower curd mitochondrial proteome was investigated under cold, heat and the recovery. For the first time, two dimensional fluorescence difference gel electrophoresis was used to study the plant mitochondrial complexome in heat and heat recovery. Particularly, changes in the complex I and complex III subunits and import proteins, and the partial disintegration of matrix complexes were observed. The presence of unassembled subunits of ATP synthase was accompanied by impairment in mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 107 publications
(148 reference statements)
5
32
1
Order By: Relevance
“…In addition, AOX may not to be increased in abundance by certain stress treatments, for example chilling [ 49 , 50 ]. The latter phenomenon was also confirmed in our previous study [ 41 ]; we reported a significant decline in AOX level in cauliflower mitochondria under cold stress and recovery. Overall AOX gene family responses on proteomic and transcriptomic levels were only partially associated and AOX was a suggested target of translational regulation in diverse temperature treatments.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, AOX may not to be increased in abundance by certain stress treatments, for example chilling [ 49 , 50 ]. The latter phenomenon was also confirmed in our previous study [ 41 ]; we reported a significant decline in AOX level in cauliflower mitochondria under cold stress and recovery. Overall AOX gene family responses on proteomic and transcriptomic levels were only partially associated and AOX was a suggested target of translational regulation in diverse temperature treatments.…”
Section: Introductionsupporting
confidence: 91%
“…Although it is known that temperature stress modulates mitochondrial protein activity, level, biogenesis and interactions [ 40 , 41 , 42 ], crucial steps of achieving appropriate coordination during mitochondrial biogenesis in stress need to be further investigated. For instance, Giegé et al [ 43 ] showed that regulation of mitochondrial biogenesis in Arabidopsis cell cultures during sugar starvation seems to be rather coordinated at the complex assembly.…”
Section: Introductionmentioning
confidence: 99%
“…In cold-tolerant chickpea genotypes, the content of unsaturated fatty acids increased during lowtemperature exposure (10°C for 5 days followed by 4°C for 2 days) (Shahandashti et al, 2013), which possibly contributed toward maintenance of membrane integrity during cold stress. Mitochondria are the most vital cell organelles and play an important role in stress tolerance mechanisms by interacting with energy-dissipating elements such as alternative oxidase (AOX) (Borecky and Vercesi, 2005;Rurek et al, 2015). In optimum conditions, plant cells carry on the cytochromemediated pathway with the help of the mitochondrial electron transfer chain, which results in ATP synthesis by using the proton motive force (Dinakar et al, 2016).…”
Section: Cellular and Physiological Mechanisms For Cold Survivalmentioning
confidence: 99%
“…Solubilized mitochondrial proteins (70-180 µg) were separated in 1.5 mm thick, 3%-11% gradient minigels, and the activities of CI, CII, and CV were detected as described previously [44,45]. To determine the amounts of respiratory complexes with immunoblotting, the BN-PAGE gels were soaked in transfer buffer (39 mM glycine, 0,0375% SDS, 20% ethanol, 48 mM Tris, pH 9.2) for 45 min.…”
Section: Blue Native-page In-gel Activity Assaysmentioning
confidence: 99%